Clinical findings, child and mother psychosocial status in functional constipation - Appak, Yeliz Çağan; Sapmaz, Şermin Yalın; Doğan, Güzide; Herdem, Ahmet; Özyurt, Beyhan Cengiz; Kasırga, Erhun (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Functional constipation (FC) is a common problem in childhood. In this study, we aimed to analyze the clinical and sociodemographic findings of patients with FC, parenting behaviors, and psychosocial states of children and parents. Materials and Methods: According to the Roma III diagnosis criteria, 32 patients with FC and 31 healthy controls were included. Patients’ clinical and sociodemographic data set associated with constipation was determined. Strengths and Difficulties Questionnaire was used to screen the emotional and behavioral problems in children. To evaluate the parents and family, Beck Depression Inventory, State-Trait Anxiety Inventory, Parental Attitude Research Instrument were used. Results: Emotional and peer problems subscale scores, parental concerns as well as over-parenting attitude were found higher in patients. Significant difference was also observed between the groups in terms of mean score of authoritarian attitude dimensions. Attitude of hostility and rejection and marital discordance was found to be significantly high in patient families. Our study revealed a decrease in the constipation rate with the increasing education level of parents, higher rate of constipation in families with less income than expenses, and lower rate of working mothers in patients with constipation. Parents’ depressive symptoms and anxiety level were determined to be considerably higher. Conclusion: A mother’s low education level, low socioeconomic level, presence of psychological symptoms, and problems of parental attitude-primarily the authoritarian attitude-increase the risk of FC occurrence. Therefore, FC patients and their families should definitely undergo a psychosocial assessment. Cite this article as: Appak YÇ, Sapmaz ŞY, Doğan G, Herdem A, Özyurt BC, Kasırga E. Clinical findings, child and mother psychosocial status in functional constipation. Turk J Gastroenterol 2017; 28: 465-70.